Comparative efficacy and safety of probiotics for the treatment of irritable bowel syndrome: a systematic review and network meta-analysis protocol - Man Yang; Yuanyuan Yu; Ping-Guang Lei; Jinqiu Yuan (BMJ Open)
Introduction Irritable bowel syndrome (IBS) is a common chronic functional gastrointestinal disorder affecting approximately 10% to 25% of the adult population. A large number of clinical trials have been conducted to evaluate the efficacy of probiotics for IBS but the results were inconsistent. Previous meta-analyses have shown that probiotics are effective for IBS, but the comparative efficacy of individual species is unclear. In addition, evidence regarding the superiority of combination over single probiotic is still lacking. We, therefore, perform this study to evaluate the comparative efficacy and safety of various species of probiotics, and combination regimens for the treatment of IBS.Methods and analysis This study is a systematic review with network meta-analysis. We will search PubMed, Scopus, The Cochrane Central Register of Controlled Trials and CINAHL for randomised controlled trials comparing probiotics with placebo or comparing different probiotics for IBS, with no language restrictions. The primary outcomes will be treatment response and global IBS-symptom score. We will initially combine included studies with traditional pairwise meta-analysis and then with random-effects network meta-analysis. We will quantify the effect of potential effect modifiers by meta-regression if appropriate. We will check the consistency assumption by testing the absolute difference between direct and indirect estimates for comparisons in closed loops. The quality of evidence will be evaluated according to the GRADE framework.Ethics and dissemination Ethical approval is not required for literature-based studies. We will disseminate the findings through publications in peer-reviewed journals and relevant conferences.PROSPERO registration numberCRD42018102101